Analysis on China's Nuclear Energy Development Path under the Goal of Peaking Carbon Emissions and Achieving Carbon Neutrality - Haiyang WANG; Jian RONG (Zhongguo dianli)
China's energy system will continue to speed up the clean and low-carbon transformation under the goal of peaking carbon emissions and achieving carbon neutrality (the dual-carbon target). Nuclear energy has the advantages of zero-emission of greenhouse gases in the production process, low carbon emission during the whole life cycle, high energy density and non-intermittency, and can help realize the transition of energy system through large-scale replacement of fossil energy. Based on an investigation of the current situation of China's energy system and the foundation of nuclear energy development, this paper summarizes the energy development goals proposed by various researches. Then an analysis is made of the development opportunities of nuclear energy in the fields of power generation, hydrogen production, district heating and water desalination, and the staged development objectives and the corresponding techniques are proposed. Furthermore, the development path of nuclear energy industry is discussed, and it is pointed out that the focus of future work should be on reposition of nuclear energy in the whole energy system, insisting on innovation-driven development, and adhering to the coordinated development of economic society. In the end, the issues that attention should be paid to are discussed, including safety and public acceptability, economy and flexibility, and some policy suggestions are proposed for the high quality development of nuclear energy industry.